2009
DOI: 10.1002/bem.20504
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term exposure to mobile phone base station signals does not affect cognitive functioning or physiological measures in individuals who report sensitivity to electromagnetic fields and controls

Abstract: Individuals who report sensitivity to electromagnetic fields often report cognitive impairments that they believe are due to exposure to mobile phone technology. Previous research in this area has revealed mixed results, however, with the majority of research only testing control individuals. Two studies using control and self-reported sensitive participants found inconsistent effects of mobile phone base stations on cognitive functioning. The aim of the present study was to clarify whether short-term (50 min)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 22 publications
4
26
1
3
Order By: Relevance
“…A GSM study by Huber et al [2003] showed a reduction in HR during waking and stage 1 sleep, whereas, Braune et al [2002] and Tahvanainen et al [2004] found no effect of GSM-EMF on the HR in randomized crossover trials. In contrast to our results, Eltiti et al [2007Eltiti et al [ , 2009 did not find an effect on HR using a base station-like UMTS signal, which had a different carrier frequency of 2020 MHz and was continuous. Based on the literature cited, we conclude that the possible influence of RF exposure on the HR is still unclear.…”
Section: Medium-term Changescontrasting
confidence: 99%
See 1 more Smart Citation
“…A GSM study by Huber et al [2003] showed a reduction in HR during waking and stage 1 sleep, whereas, Braune et al [2002] and Tahvanainen et al [2004] found no effect of GSM-EMF on the HR in randomized crossover trials. In contrast to our results, Eltiti et al [2007Eltiti et al [ , 2009 did not find an effect on HR using a base station-like UMTS signal, which had a different carrier frequency of 2020 MHz and was continuous. Based on the literature cited, we conclude that the possible influence of RF exposure on the HR is still unclear.…”
Section: Medium-term Changescontrasting
confidence: 99%
“…Of three published studies on the effects of GSM exposure on HR, two found no effect [Braune et al, 2002;Tahvanainen et al, 2004], while one showed a small reduction in HR [Huber et al, 2003]. No effects were found in two studies using UMTS exposure [Eltiti et al, 2007[Eltiti et al, , 2009.…”
Section: Introductionmentioning
confidence: 92%
“…Likewise, in a larger doubleblind study Eltiti et al [2009] could find no evidence that GSM (900 and 1800 MHz) or UMTS (2100 MHz) exposures affected performance in memory and attention tasks compared to sham for either electrosensitive or control groups.…”
mentioning
confidence: 87%
“…A replication study could find no differences between sham and UMTS signals on any cognitive tasks [Regel et al, 2006]. Likewise, in a larger doubleblind study Eltiti et al [2009] could find no evidence that GSM (900 and 1800 MHz) or UMTS (2100 MHz) exposures affected performance in memory and attention tasks compared to sham for either electrosensitive or control groups.The aim of the current study was to determine, under double-blind conditions, whether acute exposure to a typical TETRA base station signal affects cognitive functioning and/or physiological response in healthy controls and electrosensitive participants. Cognitive performance was measured using the Digit span test, Operation Span (OSPAN) and Letter Cancellation Task (LCT), which are comparable to those used by Eltiti et al [2009].…”
mentioning
confidence: 94%
“…W pracach późniejszych, w miarę poprawiania się metodyki badań dotyczących tego problemu, coraz częściej nie stwierdzano żad-nych efektów oddziaływania PEM telefonii komórko-wej na procesy poznawcze. Takie wnioski przedstawiono w większości prac z ostatnich lat [27,28,36,49,[72][73][74].…”
Section: Wpływ Pem Na Układ Krążenia I Jego Regulacjęunclassified